1993
DOI: 10.1159/000243981
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Regulation of Fetal Adipose Tissue Metabolism in the Pig: Role of Thyroxine

Abstract: This study was performed to characterize the role of thyroxine (T4) in the regulation of fetal adipose tissue metabolism. On day 70 of gestation, pig fetuses were hypophysectomized (hypoxed) by microcauterization. Both hypoxed and intact fetuses were implanted subcutaneously with T4 pellets or received no hormone replacement. Fetuses were removed by laparotomy on day 90 of gestation. Additional fetuses were hypoxed on day 70, implanted with T4 pellets on day 90 and removed on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
4
15
2
Order By: Relevance
“…Serum T4 concentrations were not increased in the hypophysectomized fetuses treated with T4 alone, compared with the untreated hypophysectomized fetuses. This finding is in contrast with those of our previous studies (3,6), where a consistent return of serum T 4 to intact values was observed in hypophysectomized fetuses treated for 3 to 14 days with T4 pellets. Serum triiodothyronine was not measured in this study because we had failed to detect measurable levels of this hormone after 20 days T4 treatment in a previous study (4).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Serum T4 concentrations were not increased in the hypophysectomized fetuses treated with T4 alone, compared with the untreated hypophysectomized fetuses. This finding is in contrast with those of our previous studies (3,6), where a consistent return of serum T 4 to intact values was observed in hypophysectomized fetuses treated for 3 to 14 days with T4 pellets. Serum triiodothyronine was not measured in this study because we had failed to detect measurable levels of this hormone after 20 days T4 treatment in a previous study (4).…”
Section: Resultscontrasting
confidence: 99%
“…Indirect evidence from a number of studies had shown that GH may antagonize lipogenesis during fetal development (2,3,(18)(19)(20)(21)(22). The results of the present study provide direct and definitive evidence that GH does antagonize or inhibit lipogenesis in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies were performed as previously de scribed [5] in 25-rnl flasks containing 2.0 ml of media. After 2 h, reactions for determination of glucose oxida tion (and lipogenesis) were stopped by the addition of 0.5 ml o f 1 N LLS04 to the media and the carbon diox ide released collected for 30 min in 0.2 ml hyaminc hydroxide contained in the suspended plastic center wells.…”
Section: Metabolic Incubationsmentioning
confidence: 99%
“…Recent evidence suggests that thyroid hormones, which are under hypothalamic/pituitary control, play an important role in regulating such development [5][6][7], Previous studies in our laboratory demon strated that removal of central endocrine in fluences by hypophvsectomy of the fetal pig on day 70 of development induced fat cell hypertrophy [3] and elevations in lipoprotein lipase (LPL) activity [3], de novo lipogcnesis [4,5], and basal and insulin-stimulated glu cose metabolism [5] while decreasing fat cell number [6] and markedly impairing hor mone-stimulated lipolvsis [4,5]. More recent ly, we observed that treatment of hypophysectomized (hypox) fetal pigs with thyroxine (T4) between days 70 and 90 or 105 of gestation augmented hypophysectomy-induced eleva tions in LPL activity [6,7], lipogenic enzyme activities [6,7], and lipogenesis [5], In con trast, hormone-stimulated lipolvsis [5] and fat cell number [6,7] were normalized in hypox fetuses following 14-or 21-day treatment with T4.…”
Section: Introductionmentioning
confidence: 99%
“…HC and T 4 are inducers of preadipocyte development [16,24], while indirect [25][26][27][28][29][30][31][32] and direct evidence [22] indicates that GH antagonizes lipogenesis during fetal adipocyte differentiation. Treatment with HC or T 4 significantly increased lipid accretion, LPL and de novo lipogenesis in hypox fetuses [16,24,28,29]. T 4 enhances lipid accretion by increasing hyperplasia of adipocytes while HC enhances hypertrophy with no influence on hyperplasia [23].…”
Section: Discussionmentioning
confidence: 99%